Māori women leading local sustainable food systems. (June 2018) - Stein, Karyn; Mirosa, Miranda; Carter, Lynette
The article explores how Māori women in Aotearoa (New Zealand) are defining their own food system and the values of the women at the heart of their community food initiatives. Using a blend of participatory and kaupapa Māori (Māori principles) research methodologies, the study took place over the course of 3 years, involving four women or case studies who manage community food initiatives, with three located in the North Island and one in the South Island of New Zealand. The article discusses the benefits of community gardens and farms, noting how they are counteracting food poverty through promoting access to local food while bringing more attention to the essential role that Indigenous women play in addressing food security issues. The case studies exemplify how Māori women are leading the way within their own whānau (families) and communities, promoting local solutions to global food issues, solutions based on their own knowledge and Māori cultural values.